Clinical, hormonal, and genetic spectrum of cryptorchidism: a comprehensive evaluation of patients referred for pediatric endocrinological assessment - Zümrüt Kocabey Sütçü; Emel Hatun Aytaç Kaplan; Hasan Önal (Journal of Pediatric Endocrinology and Metabolism, 2026)
Abstract Objectives Cryptorchidism is the most prevalent pediatric genital anomaly, yet its clinical significance often extends beyond simple anatomical maldescent. While surgical management is well-established, the necessity for holistic endocrine and genetic evaluation remains underexplored. We aimed to characterize the clinical, hormonal, and genetic landscapes of patients referred for pediatric endocrinological assessment following orchiopexy. Methods We retrospectively analyzed 99 boys referred for postoperative evaluation. Clinical findings, basal and dynamic hormonal profiles, and genetic results – including karyotype and targeted DSD gene panels – were evaluated. Results Preterm birth was recorded in 23.2 % of the cohort, and bilateral involvement was present in 50.5 %. Significant clinical findings included testicular atrophy (34.3 %), scrotal hypoplasia (18.2 %), micropenis (12.1 %), and hypospadias (10.1 %). Hormonal profiling revealed a broad spectrum of FSH (up to 85.7 mIU/mL) and AMH (0.01–71.80 ng/mL) levels. Among patients undergoing hCG stimulation testing, 72.7 % exhibited an insufficient testosterone response. Targeted DSD panel testing in a selected high-risk subgroup yielded a diagnostic rate of 45.4 %, identifying variants in SRD5A2, PTPN11, NR0B1, RAF1, POR, LHX4, and AMHR2. The prevalence of nonisolated cryptorchidism was relatively high, affecting 44.4 % of the cohort. This multisystemic involvement comprised defined syndromic diagnoses (17.2 %) and chronic comorbidities (27.3 %), predominantly endocrine disorders such as congenital hypothyroidism and growth hormone deficiency. Conclusions The high frequency of bilateral involvement, testicular atrophy, and genetic mutations suggests that many referred cases represent complex syndromic or endocrine conditions rather than isolated maldescent. Comprehensive endocrinological follow-up and targeted genetic testing are essential for early diagnosis and optimizing long-term fertility management.